الشيخ غازي محمد هاشم ومنهجه في "تبيان القرآن" - وين، لاي (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2013)
The research aims to comprehend the methodology of Al-Shaykh Ghazi Muhammad Haashim as found in his commentary entitled "Tibyaan al-Quraan". Library research and analytical methods were used to study the books which were written by or about him. However, "Tibyaan al-Quraan" was the basic source of this study. Al-Shaykh Ghazi Muhammad Haashim was influenced by the political conditions, social and academic statuses that were in his time. "Tibyaan al-Quraan" was written in simple Myanmar (Burmese) language and used clear methodology that is easy for everyone to understand. Al-Shaykh Ghazi copied the prophetic traditions and statements in Arabic, and then translated them into Myanmar (Burmese). He separated the Quranic verses into parts, then translated these into Myanmar (Burmese) before making interpretations. The study concludes that he was influenced by the linguistic method used by many commentators. He chose a combination of systems between interpretation of evidence and interpretation of opinion. He sought help from classical and contemporary interpretations. He explained the words first before starting on a general interpretation of a verse. If we examine his commentary, we can see that it provides social, linguistic and jurisprudential interpretations. In conclusion, his thinking was balanced and concerned with social, linguistic and jurisprudential issues. He tried to explain the influence of classical scholars in contemporary context to achieve a contemporary understanding, while preserving the classic and accurate elements.